PPR-DYW Protein EMP17 Is Required for Mitochondrial RNA Editing, Complex III Biogenesis, and Seed Development in Maize - Wang, Yong; Liu, Xin-Yuan; Huang, Zi-Qin; Li, Yan-Yan; Yang, Yan-Zhuo; Sayyed, Aqib; Sun, Feng; Gu, Zhi-Qun; Wang, Xiaomin; Tan, Bao-Cai (Frontiers in Plant Science, 2021)
Conversion of cytidines to uridines (C-to-U) at specific sites in mitochondrial and plastid transcripts is a post-transcriptional processing event that is important to the expression of organellar genes. Pentatricopeptide repeat (PPR) proteins are involved in this process. In this study, we report the function of a previously uncharacterized PPR-DYW protein EMP17 in the C-to-U editing and kernel development in maize. EMP17 is targeted to mitochondria. Loss-function of EMP17 arrests maize kernel development, abolishes the editing at ccmFC-799 and nad2-677 sites, and reduces the editing at ccmFC-906 and -966 sites. The absence of editing causes amino acid residue changes of CcmFC-267 (Ser to Pro) and Nad2-226 (Phe to Ser), respectively. As CcmFC functions in cytochrome c maturation, the amount of Cytc and Cytc1 protein is drastically reduced in emp17, suggesting that the CcmFC-267 (Ser to Pro) change impairs the CcmFc function. As a result, the assembly of complex III is strikingly decreased in emp17. In contrast, the assembly of complex I appears less affected, suggesting that the Nad2-226 (Phe to Ser) change may have less impact on Nad2 function. Together, these results indicate that EMP17 is required for the C-to-U editing at several sites in mitochondrial transcripts, complex III biogenesis and seed development in maize.